The labor market performance of first-generation immigrants: Evidence for Switzerland - Stefan M. Golder (Kiel Institute of World Economics (IfW), 1999)
This paper is concerned with the study of the labor market performance of immigrants. The unemployment rate is used as an indicator and natives as the reference group for the analysis. The analysis proceeds in two steps. In a first step, probit regressions on the unemployment probabilities are estimated for the pooled crosssection of 1991 and 1995, taking into account nationality- and gender-specific differences. In a second step, and based on the finding that unemployment rates usually differ significantly across sectors, the asymmetry in the sectoral distribution of immigrants with respect to natives is assessed. The empirical results indicate that Swiss and males exhibit significantly lower unemployment probabilities than immigrants and females. Furthermore, immigrants from Non-European countries have not only a higher unemployment probability than natives, but also the largest asymmetry in the employment structure.
Keywords: F22; J22; J23; J64; 330; International Migration; Labor Supply; Employment Determinantion; Unemployment; Einwanderung; Internationale Arbeitsmobilität; Arbeitslosigkeit; Geschlecht; Arbeitsmarktsegmentierung; Ausländische Arbeitskräfte; Schätzung; Welt; Schweiz